The Influence of Service Quality, Word of Mouth, Patient Physician Trust on Revisit Intentions Mediated by Patient Satisfaction in Primaya Hospital Patients - Abutar, Ariestra Utami; Dewi Sri Surya Wuisan (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This research was conducted to determine the influence of service quality, word of mouth, patient-physician trust on revisit intention which is mediated by patient satisfaction in Primaya Sorowako Hospital patients. This research is quantitative and was conducted cross-sectionally. The total sample was 119 patients. The sample was selected using non-probability sampling, namely purposive sampling. Research data was taken using Google form media with five answer choices. The data analysis method uses PLS-SEM. The results of this study found that service quality had no effect on revisit intention. Word of mouth has a positive effect on revisit intention. Patient physician trust has no effect on revisit intention. Patient satisfaction has a positive effect on revisit intention. Service quality has a positive effect on patient satisfaction. Word of mouth has a positive effect on patient satisfaction. Patient physician trust has no effect on patient satisfaction. Patient satisfaction fully mediates the positive influence of service quality on revisit intention. Patient satisfaction partially mediates the positive influence of word of mouth on revisit intention. Patient satisfaction does not mediate the influence of patient physician trust on revisit intention. The hospital can increase revisit intention by making patients feel satisfied through the various services provided at the hospital, longer consultation times, faster waiting hours, more attention given by hospital staff. Suggestions for further research could be expanded to several other hospitals in the Sorowako area and surrounding areas. Further research can also add other factors that cause high and low patient revisit intention, such as price perceptions and hospital image.